PENGARUH GREEN MAREKTING, KUALITAS PRODUK, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA STARBUCKS COFFEE DI DENPASAR - Ni Luh Putu Suwastiari; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (EMAS, 2021)
The purpose of this study is to test and obtain empirical evidence of the effect of green marketing, product quality, brand image on purchase decision This study focused on the city of Denpasar by using the purchase decisions on products Starbucks Coffee as research objects. The study involved 100 respondents using purposive sampling as a method of data collection. Data was collected through questionnaires which contain a statement - a statement which is derived from indicators - indicators in the study. Data analysis technique used in this research is multiple linear regression. The results showed that green marketing, product quality, and brand image had a positive effect on purchase decision. The results of this study can be a reference for the company to implement a policy relating to the sales strategy of products or services provided